PELANGGARAN MAKSIM (FLOUTING MAXIM) DALAM TUTURAN TOKOH FILM RADIO GALAU FM: SEBUAH KAJIAN PRAGMATIK - Niswatin Nurul Hidayati (AN-NAS, 2018)
â€œThe cooperative principle proposed by Grice stated â€œmake your contribution such as is required, at the stage at which it occurs, by the accepted purpose or direction of the talk exchange in which you are engagedâ€, but in the real life communication, this principle was often being flouted which was known as flouting maxim. This research aimed to describe the flouting maxim phenomenon in one of Indonesian films, Radio Galau FM.From the analysis of the collected data, the researcher found that some conversation of the main characters in this movie contained flouting maxim, whether it is flouting maxim of quantity, quality, relevance, and also manner. When the flouting maxim happened, it contained certain implicature, in which the speaker intended to deliver certain implicit message, such as assuring the hearer, giving surprise, asking for attention, also avoiding the conflictâ€.